Spatial analysis of the socio-educational association with delay and school dropout in regular primary education by department, Peru 2016 to 2021 - Infante Rojas, Magen Danielle (2023)
Basic Education in Peru is key factor for the development of the country. The Primary Education indicators published by the Institute of Statistics and Informatics (INEI) reveals the need for further research. Although there are various studies regarding primary education, they have not been as exhaustive as expected. For each level of basic education, the real-life situations are different, one of these levels is primary education, which the majority of Peruvians access. The objective is to establish the spatial socio-educational association of backwardness and school dropout. A data frame, called dataframe, was built with the Educational Quality Statistics (ESCALE) of the Ministry of Education (MINEDU) of Peru. In addition to spatial descriptive analysis, spatial auto-correlation at the Departmental level of backwardness and school dropout was verified, moreover, the factors chronic childhood malnutrition, children and adolescents who work and students with mothers with completed higher education are spatially associated with the backwardness and school dropout. This association was confirmed through the Weighted Spatial Regression model.